2014
DOI: 10.1519/jsc.0b013e318295d2fb
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Static and Dynamic Stretching on Sprint and Jump Performance in Boys and Girls

Abstract: The aim of this study was to investigate the acute effects of static (SS) and dynamic stretching (DS) on explosive power, flexibility, and sprinting ability of adolescent boys and girls and to report possible gender interactions. Forty-seven active adolescent boys and girls were randomly tested after SS and DS of 40 seconds on quadriceps, hamstrings, hip extensors, and plantar flexors; no stretching was performed at the control condition. Pretreatment and posttreatment tests examined the effects of stretching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 34 publications
3
46
1
13
Order By: Relevance
“…The results are in agreement with previous findings (Fletcher and Anness,2007, Fletcher and Jones, 2004, Little and Williams, 2006Nelson et al, 2005, Chaouachi et al, 2008, Paradisis et al, 2013, Vasileiou et al 2013, Papadopoulos et al, 2015, Famisis, 2015. Similar were the CMJ results.…”
Section: Discussionsupporting
confidence: 93%
“…The results are in agreement with previous findings (Fletcher and Anness,2007, Fletcher and Jones, 2004, Little and Williams, 2006Nelson et al, 2005, Chaouachi et al, 2008, Paradisis et al, 2013, Vasileiou et al 2013, Papadopoulos et al, 2015, Famisis, 2015. Similar were the CMJ results.…”
Section: Discussionsupporting
confidence: 93%
“…Most studies report that movements were performed through a full or nearly full active ROM. Stretches performed through the active or maximal ROM resulted in trivial and nonsignificant performance changes (Beedle et al 2008;Herda et al 2008;Curry et al 2009;Amiri-Khorasani et al 2010;Chaouachi et al 2010;Paradisis et al 2014), performance enhancements (Fletcher and Anness 2007;Yamaguchi et al 2007;Chaouachi et al 2010), or performance impairments (Curry et al 2009). Two studies reporting performance impairments required subjects to perform small ballistic bouncing or bobbing movements near the end ROM Bacurau et al 2009).…”
Section: Effect Of Magnitude Of Ds Movement On Performancementioning
confidence: 99%
“…Static stretching (SS) is considered an effective method for increasing joint range of motion (ROM) (Paradisis et al 2014;Power et al 2004) and is often thought to improve performance (Young and Behm 2003;Young 2007) and reduce the incidence of activity-related injuries (Ekstrand et al 1983;Hadala and Barrios 2009). It is therefore commonly performed in preactivity routines Simenz et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that neural and mechanical factors responsible for the decrement of muscular performance after static stretching (Ogura et al, 2007;Paradisis et al, 2014). Stiffer musculotendinous unit (MTU) more effective to force generated by muscles transmitted to skeletal system than compliant MTU (Kokkonen et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Active recovery and stretching between the consecutive sets are mostly used by athletes and coaches to diminish the effects of fatigue. Previous studies demonstrated that static stretching has negative effects on performance which performed after static stretching (Cornwell et al, 2002;Evetovich et al, 2003;Hough et al, 2009;Kistler et al, 2010;Kokkonen et al, 1998;Nelson et al, 2005;Paradisis et al, 2014;Pinto et al, 2014;Young and Behm, 2003). However, little research has reported the effects of stretching between sets on the number of repetitions or volume completed.…”
Section: Introductionmentioning
confidence: 96%